Positive Parenting Styles in Educating Alpha-Generation Children in the Industrial Revolution 4.0 Era - Iis Sintiani; Nur Faizah Romadona (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
An intangible piece of gold can be beautiful if it is carved by an expert carver, and young children will become good individuals who grow and develop well shall their parents are knowledgeable about good parenting patterns. The alpha generation comprises individuals born in 2013 and above. This generation faces the Industrial Revolution 4.0 era, in which such a revolution is a phenomenon collaborating cyber and automatization technologies, meaning that all things are applied using technologies that reduce human involvement in the process. Parents should understand parenting style in educating alpha-generation children facing the Industrial Revolution 4.0 era. This parenting style is definitely different than parenting styles of previous generations. Therefore, the study aimed to understand a good parenting style for alpha-generation children in encountering the Industrial Revolution 4.0 era. The study method was systematic review, where researchers documented and processed various sources, such as articles, books, and documents concerning positive parenting styles in educating the alpha generation and facing the Industrial Revolution 4.0 era.